2020
DOI: 10.1016/j.apenergy.2020.114998
|View full text |Cite
|
Sign up to set email alerts
|

Optimal design and performance analysis of a hybrid system combing a floating wind platform and wave energy converters

Abstract: Combined floating offshore wind platform and wave energy converter (WECs) systems have the potential to provide a cost-effective solution to offshore power supply and platform protection. The objective of this paper is to optimize the size and layout of WECs within the hybrid system under a given sea state with a numerical study. The numerical model was developed based on potential flow theory with viscous correction in the frequency domain to investigate the hydrodynamic performance of a hybrid system consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(66 citation statements)
references
References 32 publications
6
56
1
3
Order By: Relevance
“…In the following sections, different DDRs of 2r/d are chosen, where d 1.0 m. The investigation of Hu et al (2020) showed that f λ,vist generally decreased to approach 1.0 as the ratio 2r/d increased. It meant that the viscous effect became smaller as the WEC became fatter, such that the viscous effect of a very fat floater is negligible.…”
Section: Flat Bottommentioning
confidence: 99%
“…In the following sections, different DDRs of 2r/d are chosen, where d 1.0 m. The investigation of Hu et al (2020) showed that f λ,vist generally decreased to approach 1.0 as the ratio 2r/d increased. It meant that the viscous effect became smaller as the WEC became fatter, such that the viscous effect of a very fat floater is negligible.…”
Section: Flat Bottommentioning
confidence: 99%
“…There are many articles using combined FOWT and Wave Energy Converters (WEC) to create a multi-purpose platform that absorbs both wind and wave energies [27][28][29][30][31]. However, there are a few articles proposing OWCs included in FOWTs with stabilization as the main objective.…”
Section: Introductionmentioning
confidence: 99%
“…The most studied platform is wind-wave platforms that combine wind turbines and WEC to harness the wave and wind energies [19][20][21]. The use of the OWC with a floating offshore wind turbine has been proposed and shown promising results.…”
Section: Introductionmentioning
confidence: 99%